2004
DOI: 10.1074/jbc.m404020200
|View full text |Cite
|
Sign up to set email alerts
|

Rad23 and Rpn10 Serve as Alternative Ubiquitin Receptors for the Proteasome

Abstract: The selective recognition of ubiquitin conjugates by proteasomes is a key step in protein degradation. The receptors that mediate this step have yet to be clearly defined although specific candidates exist. Here we show that the proteasome directly recognizes ubiquitin chains through a specific subunit, Rpn10, and also recognizes chains indirectly through Rad23, a reversibly bound proteasome cofactor. Both binding events can be observed in purified biochemical systems. A block substitution in the chain-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
292
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(297 citation statements)
references
References 49 publications
(61 reference statements)
4
292
0
1
Order By: Relevance
“…RP1CP and RP2CP refer to singly or doubly 19 S capped 20 S proteasomes, respectively. Active proteasome was purified and analyzed by nondenaturating PAGE as described (61). C, a siRNA-mediated knockdown of hRpn10 does not affect parkin binding to proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…RP1CP and RP2CP refer to singly or doubly 19 S capped 20 S proteasomes, respectively. Active proteasome was purified and analyzed by nondenaturating PAGE as described (61). C, a siRNA-mediated knockdown of hRpn10 does not affect parkin binding to proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotes, the DNA repair proteins Rad23 and Dsk2 can target ubiquitinated proteins for degradation [63,64]. They interact with the proteasome through a ubiquitin-like domain (UBL) and with the ubiquitin modification in substrates through two ubiquitinassociation domains (UBAs) [37,38,63,[65][66][67]. Thus, UBL-UBA proteins appear to deliver ubiquitinated proteins to the proteasome where they are subsequently degraded.…”
Section: Adapter Proteinsmentioning
confidence: 99%
“…On the contrary, recent work has shown that a diverse set of ubiquitin-binding receptors regulate the targeting of ubiquitinated proteins to the proteasome in a substratespecific manner (Wilkinson et al, 2001;Chen and Madura, 2002;Elsasser et al, 2004;Verma et al, 2004; for review, see Elsasser and Finley, 2005;Hicke et al, 2005). The first polyubiquitin-binding receptor identified was Rpn10, a subunit of the 19S regulatory complex that contains a ubiquitin-interacting motif (Deveraux et al, 1994 tional ubiquitin chain recognition mechanisms must exist (van Nocker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%